Police Leadership as Practice - Filstad, Cathrine, 1963- (New York, NY : Routledge, 2022)
"Police Leadership as Practice applies a leadership-as-practice approach (emphasising leader-employee relationships) to law enforcement. This book provides a progressive and collaborative leadership text for students of law enforcement, as well as insights into leadership dynamics in all organizations for students and researchers of business and management. The Police leadership-as-practice perspective provides a holistic understanding of leadership in the police, identifying factors that inhibit and promote learning. It refers to four main components as dynamic and continuously evolving processes: Strategies: social mission and organization, along with strategies as practice. Community: organizational and police culture, identity and belonging, community of practice and competencies. Participation: sense-making and discretion; power and politics. Activities: learning as practice, change and change management as practice Practical and enriched with case studies, examples and best practice, the textbook is also rigorously research based. Authored by a professor of business and management with specialist knowledge in police leadership, it brings the cutting edge of leadership thinking to the practicalities of policing. It is essential reading for those engaged with policing, leaderships roles and management"--
Includes bibliographical references and index.
Keywords: Police; Law enforcement; Leadership; Organizational learning